Editorial: On Poverty and Its Eradication - Andrzej Klimczuk; Guillermina Jasso; Mariah D. R. Evans; Jonathan Kelley (Frontiers in Sociology, 2024)
The Research Topic “On poverty and its eradication” was inspired by the International Day for the Eradication of Poverty, first commemorated in Paris in 1987 and formally designated by the United Nations. This day is dedicated to renewing the commitment to universal human development, enabling all individuals to achieve their highest potential, and reflecting on how poverty hinders this progress. The urgency of addressing poverty has increased after the COVID-19 pandemic, which exacerbated existing issues and highlighted the critical need for effective poverty eradication strategies. The studies included in this Research Topic aim to expand knowledge about poverty, its causes, consequences, and connections to crises, inequality, and fairness, and to assess policy measures for poverty reduction. The included contributions use various theoretical, empirical, quantitative, and qualitative approaches to drive sociological and policy-related discussions and initiatives, promoting fair and inclusive societies.
Keywords: I30; I32; I38; D60; 330; poverty; poverty relief; poverty and inequalities; poverty and fairness; poverty and public policy